Effects of reproductive condition on haemocyte parameters in the Pacific abalone Haliotis discus hannai during the spawning period - Pantip Sawangwong; Nan Chen; Xuan Luo; Grace Afumwaa Boamah; Jin‐Chywan Gwo; Caihuan Ke; Weiwei You (New Zealand Journal of Marine and Freshwater Research, 2025)
The assessment of morphology and immunology of specimens at different maturity stages is essential for the determination of spawning strategy and reducing the risk of mortality. In this paper, female and male Pacific abalones ( Haliotis discus hannai ) at different statuses (pre‐spawning, spawning and post‐spawning) were collected to estimate the effects of spawning on the immune response. The haemocyte parameters, including total haemocyte counts (THC), haemocyte mortality, and reactive oxygen species production (ROS) were analysed using flow cytometry. THC decreased after spawning, which was lowest 3 days post‐spawning. Haemocyte mortality was higher during spawning, and was highest 3 days post‐spawning. Abalone also reduced their metabolic activity after spawning, reflected by an increase in ROS in both females and males. Moreover, our results show that female abalone reach the spawning period with a higher degree of activities of haemocytes and immune responses than male. The results confirmed that variability in abalone haemocytes during the spawning period might related to individual metabolic conditions.